The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1097/sla.0b013e31828ee17c
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transplantation for Neuroendocrine Tumors in Europe—Results and Trends in Patient Selection

Abstract: LT is an effective treatment of unresectable LM from NET. Patient selection based on the aforementioned predictors can achieve a 5-year OS between 60% and 80%. However, use of overly restrictive criteria may deny LT to some patients who could benefit. Optimal timing for LT in patients with stable versus progressive disease remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
237
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(259 citation statements)
references
References 25 publications
6
237
1
3
Order By: Relevance
“…The only prospective study recommended strict selection criteria for LT with curative intent (i.e., low grade, removal of primary tumor, liver involvement < 50%, age < 55 years, and stable disease for ≥ 6 mo before LT) [21] , and a study reported 96% overall survival and 80% disease-free survival [22] . However, it was also reported that P-NET patients with liver metastases who received LT had a follow-up term of no longer than 5.8 years, and the longest tumor-free survival was 5.1 years [23] , and a high rate of tumor recurrence was reported at almost 60% [20] . Use of LT for extended indications always presents an ethical dilemma [10] .…”
Section: Lt For Unresectable Liver Metastasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The only prospective study recommended strict selection criteria for LT with curative intent (i.e., low grade, removal of primary tumor, liver involvement < 50%, age < 55 years, and stable disease for ≥ 6 mo before LT) [21] , and a study reported 96% overall survival and 80% disease-free survival [22] . However, it was also reported that P-NET patients with liver metastases who received LT had a follow-up term of no longer than 5.8 years, and the longest tumor-free survival was 5.1 years [23] , and a high rate of tumor recurrence was reported at almost 60% [20] . Use of LT for extended indications always presents an ethical dilemma [10] .…”
Section: Lt For Unresectable Liver Metastasesmentioning
confidence: 99%
“…Several attempts to implement this strategy between 1960 and the 1980s showed poor results, although LT for early hepatocellular carcinoma has been established [18] . It is well known that highly selected P-NET patients with liver metastases may be candidates for LT [10,[19][20][21] . The only prospective study recommended strict selection criteria for LT with curative intent (i.e., low grade, removal of primary tumor, liver involvement < 50%, age < 55 years, and stable disease for ≥ 6 mo before LT) [21] , and a study reported 96% overall survival and 80% disease-free survival [22] .…”
Section: Lt For Unresectable Liver Metastasesmentioning
confidence: 99%
“…[80][81][82][83][84] Recently, a European registry study described outcomes of 213 cases that underwent LT for metastatic NET, the largest number of patients to date; 5-y overall and disease-free survival rates were 52% and 30%, respectively. 85 Hepatomegaly, poor tumor differentiation, and major resection concurrent with LT were revealed to be poor prognostic indicators and better survival rates of nearly 60% were achieved in cases performed after 2000 because of more favorable patient characteristics. 85 There is a growing consensus that LT for metastatic NET should be considered for unresectable disease, no extrahepatic disease, welldifferentiated NET (NET G1/G2), and should not be associated with major extrahepatic resection.…”
Section: Metastatic Liver Tumors Neuroendocrine Tumor (Net)mentioning
confidence: 99%
“…85 Hepatomegaly, poor tumor differentiation, and major resection concurrent with LT were revealed to be poor prognostic indicators and better survival rates of nearly 60% were achieved in cases performed after 2000 because of more favorable patient characteristics. 85 There is a growing consensus that LT for metastatic NET should be considered for unresectable disease, no extrahepatic disease, welldifferentiated NET (NET G1/G2), and should not be associated with major extrahepatic resection. 85 Medical treatment continues to evolve and the timing of LT remains controversial.…”
Section: Metastatic Liver Tumors Neuroendocrine Tumor (Net)mentioning
confidence: 99%
See 1 more Smart Citation